P53 immunohistochemical analysis of fusion‐positive uterine sarcomas. Issue 6 (14th February 2021) - Mohammad, Nissreen; Stewart, Colin J R; Chiang, Sarah; Turashvili, Gulisa; Dickson, Brendan C; Ng, Tony L; Köbel, Martin; McCluggage, W Glenn; Croce, Sabrina; Lee, Cheng‐Han
Abstract : Aims: Uterine sarcomas can be grouped into tumours with pathognomonic genetic fusions such as low‐grade endometrial stromal sarcoma (LGESS), high‐grade endometrial stromal sarcoma (HGESS), and inflammatory myofibroblastic tumour (IMT), and tumours lacking genetic fusions such as leiomyosarcoma (LMS) and undifferentiated uterine sarcoma (UUS). Members of the latter group frequently harbour TP53 mutations. The aim of this study was to evaluate TP53 mutations by the use of immunohistochemistry in fusion‐positive uterine sarcomas. Methods and results: We performed p53 immunohistochemical staining on 124 uterine sarcomas harbouring genetic fusions and 38 fusion‐negative LMSs and UUSs. These included 41 HGESSs with YWHAE, BCOR and BCORL1 fusions/rearrangements, 13 IMTs with ALK fusion, 12 sarcomas with NTRK1 / 3 fusion, three sarcomas with PDGFB fusion, and 55 LGESSs with JAZF1, SUZ12 and PHF1 fusions/rearrangements. All HGESSs, LGESSs, IMTs and sarcomas with PDGFB fusion showed wild‐type p53 expression. Among NTRK1 / 3 ‐positive sarcomas, a TPR – NTRK1 ‐positive sarcoma with nuclear pleomorphism showed mutation‐type p53 expression. The remaining 11 NTRK1 / 3 ‐positive sarcomas showed wild‐type p53 expression, except for the subclonal p53 mutation‐type staining in a minor pleomorphic focus of an NTRK3 ‐positive sarcoma. Twenty‐one of 27 (78%) LMSs and six of nine (67%) UUSs showed mutation‐type p53 expression. Conclusion: p53 immunohistochemistry may be considered in the initial work‐up of a uterine sarcoma, as mutation‐type staining would make a fusion‐positive sarcoma very unlikely. Mutation‐type p53 expression, however, can be seen in a small subset of NTRK1 / 3 ‐positive sarcomas showing pleomorphic round/ovoid cell histology, which may represent a mechanism of progression in these tumours. Abstract :